Lower body training the definitive guide to increasing size, strength, and athletic performance - Brown, Jason 1983- (Champaign, IL Human Kinetics, 2023)
"A comprehensive guide to lower body training that will contain everything from the classification of exercises based on the specific lower body movement patterns that they target, to bio-mechanical "hacks" for making staple exercises even more effective, to expert programming for readers with wide ranging goals. The book will be appealing to readers who are seeking the most up-to-date, scientifically proven strategies for increasing lower body size, strength, and power"--
Foreword -- Acknowledgments -- Introduction -- Part I. The scientific approach to lower-body training. Meet the muscles -- Create better balance through movement -- Go beyond the basics -- Set realistic training goals -- Part II. The exercises. Quad-dominant exercises -- Hip-dominant exercises -- Isolation exercises -- Plyometric exercises -- Part III. The programs. Hypertrophy programs -- Strength programs -- Athletic performance programs -- At-home training programs.
Includes bibliographical references.
Description based on print version record and CIP data provided by publisher.
Keywords: Exercise; Physical education and training; Physical fitness -- Physiological aspects